REKONSTRUKSI KEWENANGAN KOMISI YUDISIAL TERHADAP PENGUSULAN HAKIM KONSTITUSI SEBAGAI UPAYA PENINGKATAN NETRALITAS HAKIM KONSTITUSI DI INDONESIA - Muhammad Fauzan; Yacub, Tifanny Nur; Gumilar, Egi Rivaldi; Safitri, Nadila; Sitanggang, Matthew Jakaria (Esensi Hukum, 2023)
The Judicial Commission is an institution that was born as a result of demands for reform of the judiciary in Indonesia. The existence of the KY is not only limited to what is contained in the constitutional mandate, but is an external institution that has duties related to judicial oversight. More than that, the KY has a role in carrying out the function of checks and balances so that in the judicial power conditions can be created that are balanced, independent and free. Along his journey, KY experienced twists and turns. For example, the resistance of Supreme Court justices as externally supervised subjects, adjudication efforts at the Constitutional Court which weaken the role of the Judicial Commission as an external institution, and the authority to appoint and appoint Supreme Court judges, has made the Judicial Commission farther and farther away from realizing a clean and noble judiciary within the judiciary. The method used in this study is normative juridical with a statutory approach, a conceptual approach, and a case approach. The resulting conclusion is that through the reconstruction of the KY's authority, it is hoped that proposals for the appointment of constitutional judges can be based more on clear and transparent criteria and procedures, as well as taking into account the integrity and competence of prospective constitutional judges. In addition, to realize this, it is necessary to amend the 1945 Constitution of the Republic of Indonesia by amending the provisions of Article 24B paragraph (1) and Article 24C paragraph (3). These changes extend to laws, such as the Constitutional Court Law, the Supreme Court Law, and the Judicial Commission Law.